Differential gene expression in seasonal sympatry: mechanisms involved in diverging life histories - Fudickar, Adam M. (Biol Lett, 2016)
In an era of climate change, understanding the genetic and physiological mechanisms underlying flexibility in phenology and life history has gained greater importance. These mechanisms can be elucidated by comparing closely related populations that differ in key behavioural and physiological traits such as migration and timing of reproduction. We compared gene expression in two recently diverged dark-eyed Junco ( Junco hyemalis) subspecies that live in seasonal sympatry during winter and early spring, but that differ in behaviour and physiology, despite exposure to identical environmental cues. We identified 547 genes differentially expressed in blood and pectoral muscle. Genes involved in lipid transport and metabolism were highly expressed in migrant juncos, while genes involved in reproductive processes were highly expressed in resident breeders. Seasonal differences in gene expression in closely related populations residing in the same environment provide significant insights into mechanisms underlying variation in phenology and life history, and have potential implications for the role of seasonal timing differences in gene flow and reproductive isolation.